How European Big Science Organizations and Suppliers Innovate through Public Procurement: The five modes of innovation identified in the Big Science Organization-supplier relationship can help facilitate and spur collaborative innovation. Issue 2 (23rd January 2021) - Li-Ying, Jason; Forneris, Juliette; Korsholm, Søren Bang; Jensen, Arne; Zangenberg, Nikolaj
Overview: Big Science Organizations (BSOs) increasingly influence innovation and business creation, yet limited knowledge exists currently about how they innovate collaboratively with industrial suppliers. We present five innovation modes in the BSO-supplier relationship; identify pre- and post-contracting challenges for BSOs and suppliers; identify the primary solvers; and highlight the best practices of BSOs, suppliers, and industrial liaison offices to overcome these challenges. Managers at BSOs and industrial suppliers can use the lessons learned to understand fully the fundamentals of collaborative innovation between BSOs and suppliers.